Anticancer Effect of Sapindus trifoliatus on Human Breast Cancer Cell Lines - D. Pradhan; V.Joshi; G.Tripathy (International Journal of Pharma and Bio Sciences, 2010)
Evaluation of anticancer effect of Sapindus trifoliatus (family- Sapindaceae) which has long been prescribed for various infectious and malignant diseases. Bio-assays of extracts from Sapindus trifoliatus showed that a fraction (fraction 3) from an ethanolic extract had an antiproliferative effect on SKBR3 and MDA-MB435 human breast cancer cells. The ED50 value of Sapindus trifoliatus, fraction 3 was 56.07 and 30.61 μg/ml for SKBR3 and MDA-MB435, respectively. After 48 h of exposure, this fraction at a concentration of 100 μg/ml significantly reduced cell proliferation in both cancer cells. In MDA-MB435 cells, cell cycle analysis showed that the herb extract fraction 3 induced the accumulation of cells in G2/M phase, whereas no significant change in cell cycle was detected in SKBR3 cells. The results indicated that the extract fraction could induce cell cycle arrest in some way. However, further investigation is needed to assess the molecular mechanisms mediated anticancer activities of this plant.